Annual Plan 1997-98 State Planning Commission Tamil Nadu - Planning Commission (Planning Commission, 1997)
The north-east monsoon which usually sets in the third week of October every year, had advanced by 10 days during this year. On the positive side, the monsoon brought in good inflows to the State’s surface flow sources of irrigation and helped in improving the recharging capacity of ground water sources. On the negative side, it had caused damages to the standing crops in the coastal districts of the State, viz., Chengalpattu-MGR, Anna, South Arcot Vallalar, North Arcot Ambedkar, Thanjavur and Nagappattinam Quaid-E-Milleth. Due to excess precipitation at the fag end of the monsoon, an extent of 3,08,112 hectares under various standing crops had been completely damaged and partial damage had been caused to crops in 2,20,903 hectares. Further, horticulture crops were totally damaged over an extent of 15,437 hectares and partially damaged over an extent of 6,626 hectares. To mitigate these crop loss, farmers were compensated based on the extent of crop damage. However, the north-east monsoon had brightened the prospects of the standing crops and the ensuing summer crops.
Annual Plan 1997-98
Government of Tamil Nadu